ASSRJ 2018
DOI: 10.14738/assrj.53.4240
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Of Child Labour Practices In Urban And Rural Communities In Cross River State, Nigeria

Abstract: The study was aimed at identifying child labour practices existing in urban and rural areas in Cross River state. The study utilized survey design while cluster random sampling and purposive sampling technique was used to select samples, questionnaires and key informant interview were deployed for data collection. The analysis of data involved use of percentages and transcription of views of the key informants. The study discovered that child labour practices in urban areas of Cross River state include domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…33 In Cross River State, engaging as a house-help was the highest child labour practice followed by hawking in the urban region. 31 Other studies in Nigeria also reported house-help as the most common child labour practice in urban areas. 1,9 However, some studies found farming as the most prominent child labour practice in the rural area.…”
Section: Facts and Figures By The Ilo Indicate That Childmentioning
confidence: 98%
See 2 more Smart Citations
“…33 In Cross River State, engaging as a house-help was the highest child labour practice followed by hawking in the urban region. 31 Other studies in Nigeria also reported house-help as the most common child labour practice in urban areas. 1,9 However, some studies found farming as the most prominent child labour practice in the rural area.…”
Section: Facts and Figures By The Ilo Indicate That Childmentioning
confidence: 98%
“…This finding is similar to that of children who worked in the urban cities and towns in Cross River State who were paid for their services, unlike their counterparts in rural areas. 31 Other kinds of payments received by about one-fifth of children in both urban and rural settings are provision of accommodation and upkeep. Another study found that children in rural areas work for their families, and hence most are not paid in cash for the services.…”
Section: Facts and Figures By The Ilo Indicate That Childmentioning
confidence: 99%
See 1 more Smart Citation
“…ASUU, over time, has emerged as a vital force for quality education and socio-economic transformation (Marcus, Kabiru, Solomon & Akhimen, 2017). While some studies highlight the positive impact of ASUU on workers' productivity, pro-governmental viewpoints argue that the union, particularly due to its strikes, is detrimental to the quality of university education (Odey & Sambe, 2018). In light of this ongoing debate, the study aims to investigate the impact of trade unionism, specifically ASUU-Federal Government disputes, on productivity and educational development in Uniport, Rivers State University, Delta State University, Abraka, and the Niger Delta University.…”
Section: Introductionmentioning
confidence: 99%
“…May 2023 edition Vol 19,. No.13 www.eujournal.org 88 There is no significant difference in educated parents' practice of child labour based on income…”
mentioning
confidence: 99%